Retinoic acid receptor-β is downregulated in hepatocellular carcinoma and cirrhosis and its expression inhibits myosin-driven activation and durotaxis in hepatic stellate cells - Cortes,E; Lachowski,D; Rice,A; Chronopoulos,A; Robinson,B; Thorpe,S; Lee,DA; Possamai,LA; Wang,H; Pinato,DJ; Del,Río Hernández AE (Hepatology, 2019)
Hepatic stellate cells (HSCs) are essential perisinusoidal cells in the healthy and diseased liver. HSCs modulate extracellular matrix (ECM) homeostasis when quiescent, but in liver fibrosis, HSCs become activated and promote excess deposition of ECM molecules and tissue stiffening via force generation and mechanosensing. In hepatocellular carcinoma (HCC), activated HSCs infiltrate the stroma and migrate to the tumor core to facilitate paracrine signalling with cancer cells. Since the function of HSCs is known to be modulated by retinoids, we investigated the expression profile of retinoic acid receptor beta (RAR-β) in cirrhotic and HCC patients, as well as the effects of RAR-β activation in HSCs. We found that RAR-β expression is significantly reduced in cirrhotic and HCC tissues. Using a comprehensive set of biophysical methods combined with cellular and molecular biology, we have elucidated the biomechanical mechanism by which all trans-retinoic acid (ATRA) promotes HSC deactivation via RAR-β-dependent transcriptional downregulation of myosin light chain 2 (MLC-2) expression. Furthermore, this also abrogated mechanically driven migration towards stiffer substrates. CONCLUSION: Targeting mechanotransduction in HSCs at the transcriptional level may offer new therapeutic options for a range of liver diseases. This article is protected by copyright. All rights reserved.